Implementing a Multidisciplinary Prone Positioning Team. Issue 6 (June 2021) - Elpern, Ellen H.; Nedved, Patricia; Weiss, Tyler; Patel, Ankeet D.; Cerda, Flor
ABSTRACT: The coronavirus disease 2019 pandemic has escalated clinical needs while interrupting regular processes and straining resources. Striving to deliver optimal care to infected patients with respiratory failure, Rush University Medical Center in Chicago created a multidisciplinary team to provide manual prone positioning safely and efficiently. Team members' experiences, which they shared through a survey, help to illustrate the advantages of a multidisciplinary approach and suggest opportunities to enhance the effectiveness of such a team. Abstract : The authors describe their institution's response to the rapid influx of COVID-19 patients who required prone positioning.